2020
DOI: 10.1097/01.jaa.0000660156.17502.e6
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and satisfaction with work-life integration among PAs relative to other workers

Abstract: Objective: To evaluate burnout and satisfaction with work-life integration among physician assistants (PAs) compared with other US workers. Methods: We surveyed PAs and a probability-based sample of US workers. The survey included the Maslach Burnout Inventory and an item on satisfaction with work-life integration. Results: Overall, 41.4% of PAs had burnout symptoms and 65.3% were satisfied with their work-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 47 publications
2
50
1
Order By: Relevance
“…A large body of research has indicated that the risk of burnout among physicians and other health care workers is high ( van Vendeloo et al, 2018 ; Dyrbye et al, 2020 ; Woo et al, 2020 ). The COVID-19-pandemic has further increased the risk of burnout among health care workers ( Chirico et al, 2021 ; Magnavita et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has indicated that the risk of burnout among physicians and other health care workers is high ( van Vendeloo et al, 2018 ; Dyrbye et al, 2020 ; Woo et al, 2020 ). The COVID-19-pandemic has further increased the risk of burnout among health care workers ( Chirico et al, 2021 ; Magnavita et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 A substantial body of literature supports that burnout is associated with detrimental outcomes among HCWs and for the quality of care provided to patients. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 Factors that may contribute to burnout, such as excessive workload, administrative burdens, inadequate technology usability, constrained flexibility, and poor leadership, may also erode professional satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Drivers associated with burnout among cardiologists include lack of control over workload, a hectic work environment, misalignment of values, and insufficient documentation time [ 19 ]. Data among U.S. physicians from all different specialties demonstrated that 39.8% reported burnout and 42.7% satisfaction with WLI, whereas other data among physician assistants and nurses have shown lower burnout rates (35.8% and 29.7%, respectively) and higher WLI rates (65.3% and 55.5%, respectively) [ 20 21 22 ]. There is a dearth of survey data specific to cardiovascular professionals; however, the drivers of burnout among cardiologists may likely be extrapolated to the cardiovascular workforce.…”
Section: Cardiology Burnout Datamentioning
confidence: 99%